Participatory Approaches and Conservation of Medicinal Plants: Identifying priority species in the community of Areais da Ribanceira (Brazil) - Zank, Sofia; Hanazaki, Natalia; Santos de Mello, Anderson (Ethnobotany Research and Applications, 2015)
Using a participatory approach, we aimed to identify medicinal conservation priority plant species in a region where a sustainable conservation area is being proposed. Local farmers consensually selected 10 ethno-species represented by 11 scientific species (Calea uniflora Less., Equisetum giganteum L., Aristolochia triangularis Cham., Zollernia ilicifolia (Brongn.) Vogel, Maytenus ilicifolia Mart. ex Reissek, Stachytarpheta cayennensis (Rich.) Vahl, Mikania laevigata Sch.Bip. ex Baker, Achyrocline satureioides (Lam.) DC., Lepidium didymum L., Dioscorea altissima Lam., and Picrasma crenata Engl. in Engl. & Prantl), which were the focus of two participatory tools: four-cell analysis and matrix of plants and environments. Most plants were classified as having high environmental availability and as being under intense extraction pressure. Both natural areas (restinga and hillside forest) and cultivated areas (croplands and homegardens) are important for the acquisition of native medicinal plants. This participatory process tends to facilitate the incorporation of research results by the community, according to its local demands, as well as allowing for a collective learning experience. The use of a participatory approach also allowed the gradual increase in the awareness of the community related to their medicinal plants, contributing to their own decisions about the management and conservation of these resources.